Through the Years: Narratives of Pamantasan ng Cabuyao (PnC) Towards the Development of a Coffee Table Book - Lamis, Eruel A. (International Journal on Integrated Education, 2025)
Every Institution has its great story to be told, a tapestry to share, and a culture to pass through the years. This research delves into the historical narratives of Pamantasan ng Cabuyao with the goal of laying the groundwork for a coffee table book that captures the university’s rich legacy. Founded in the context of providing accessible and quality higher education in Cabuyao City, the university has grown into a symbol of resilience and academic excellence. The study aimed to document and interpret personal and institutional stories that reflect the university’s development, challenges, and milestones over time. Using narrative inquiry as the primary method, data was collected through in-depth narrative interviews with selected stakeholders, including administrators, faculty members, and alumni. Their shared experiences provided valuable insights into the university’s evolution and cultural identity. Findings highlight that the institution's growth is anchored in core values such as Personal dignity, Nurturing community, and a Commitment to excellence—qualities that embody its title “Dangal ng Bayan.” The narratives uncovered both structural progress and deeply personal accounts that enriched the collective memory of the university. The research concludes that these stories serve as vital elements of institutional heritage and contribute meaningfully to fostering unity and pride among members of the community. As a result, the creation of a coffee table book is recommended as a compelling medium to preserve and celebrate these narratives, while also encouraging continued efforts in historical documentation and cultural preservation.